1995
DOI: 10.1002/j.1460-2075.1995.tb07031.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the active region of the DNA synthesis inhibitory gene p21Sdi1/CIP1/WAF1.

Abstract: The cloning of the negative growth regulatory gene, p21Sdi1, has led to the convergence of the fields of cellular senescence, cell cycle regulation and tumor suppression. This gene was first cloned as an inhibitor of DNA synthesis that was overexpressed in terminally non‐dividing senescent human fibroblasts (SD11) and later as a p53 transactivated gene (WAF1) and a Cdk‐interacting protein (CIP1, p21) that inhibited cyclin‐dependent kinase activity. To identify the active region(s) of p21Sdi1, cDNA constructs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
114
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 33 publications
(25 reference statements)
9
114
0
2
Order By: Relevance
“…p21 can also associate with PCNA (Flores-Rozas et al, 1994) and inhibit DNA synthesis (Noda et al, 1994;Waga et al, 1994) but not DNA repair in vitro Shivji et al, 1994). The PCNAbinding region (around amino acids 142 ± 164) lies at the very C-terminus of p21 (Chen et al, 1995;Goubin and Ducommun, 1995;Luo et al, 1995;Nakanishi et al, 1995;Warbrick et al, 1995), as revealed by the crystal structure of a 22 residue peptide derived from the C-terminus of p21 in complex with PCNA (Gulbis et al, 1996). The PCNA-binding site overlaps the nuclear localization signal (residues 140 ± 156) and the C-terminal cyclin-binding site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…p21 can also associate with PCNA (Flores-Rozas et al, 1994) and inhibit DNA synthesis (Noda et al, 1994;Waga et al, 1994) but not DNA repair in vitro Shivji et al, 1994). The PCNAbinding region (around amino acids 142 ± 164) lies at the very C-terminus of p21 (Chen et al, 1995;Goubin and Ducommun, 1995;Luo et al, 1995;Nakanishi et al, 1995;Warbrick et al, 1995), as revealed by the crystal structure of a 22 residue peptide derived from the C-terminus of p21 in complex with PCNA (Gulbis et al, 1996). The PCNA-binding site overlaps the nuclear localization signal (residues 140 ± 156) and the C-terminal cyclin-binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Residues *10 ± 80 of p21, p27 Kip1 and p57 Kip2 are related in sequence, and this region has been identi®ed as the cyclin and CDK-binding region (Chen et al, 1995;Goubin and Ducommun, 1995;Luo et al, 1995;Nakanishi et al, 1995). Within this region, there are separate domains for binding to cyclin (residues 16 ± 24) (Adams et al, 1996;Ball et al, 1997;Chen et al, 1996;Zhu et al, 1995) and to CDK (residues 45 ± 65) (Ball et al, 1997;Goubin and Ducommun, 1995;Nakanishi et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino end of p21 WAF1/CIP1 contains an inhibitory domain of cdk, which inhibits cyclin D and E associated cdks activities. The carboxyl end of p21 WAF1/CIP1 mediates the PCNA-binding and activity of DNA polymerase d (Chen et al, 1995;Luo et al, 1995;Nakanishi et al, 1995;Warbrick et al, 1995). Our results showed that p21 WAF1/CIP1 inhibited [ 3 H]thymidine incorporation and reduced cdk2 kinase activity in human liver cancer cells but did not affect expression of cdk2 and cdk4.…”
Section: Discussionmentioning
confidence: 67%
“…Deletion anal-ysis has identified two separate domains within the 164-amino acid human p21 coding sequence. Residues 1-71 alone are highly active in CDK binding and inhibition, and residues 141-160 efficiently bind PCNA and inhibit SV40 DNA replication in vitro (Chen et al, 1995;Luo et al, 1995;Nakanish et al, 1995). To provide a structural basis for the biochemical properties of p2 I , we have purified recombinant p2 1 on a large scale to near homogeneity.…”
mentioning
confidence: 99%